COMPARISON OF THE QUALITY OF COCOA SEED FERMENTATION WITH THE ADDITION OF MIXED CULTURE AND SINGLE CULTURE OF Lactobacillus plantarum - Arita Putri Handayani; Andree Wijaya Setiawan; Yoga Aji Handoko (Fapetrik-UMPAR, 2022)
The cocoa bean fermentation process is carried out to improve the quality of cocoa beans as industrial raw materials such as the formation of aroma, color, flavor and can increase the selling value. This study aims to examine the quality of the results of the addition of mixed culture and single culture Lactobacillus plantarum and determine the best quality of fermented cocoa beans with the addition of mixed culture and single culture Lactobacillus plantarum. The cocoa beans used for fermentation were RCC clones from Nglanggeran, Gunung Kidul. This study used a randomized block design (RAK) with different concentrations of yeast and bacteria, namely: single culture 5%, 10%, 15% and mixed culture 5%, 10%, 15% with a long fermentation time for 6 days. Cocoa beans without yeast and bacteria inoculum were used as controls. The single culture and the mixed culture used influenced the different results. The best treatment using a single culture was a single culture of 10%, while the treatment with the addition of mixed cultures was a mixed culture of 10%. The results of the research analysis of some of the best parameters as follows: 37.85?C temperature measurement; pH 5.37; yield 31,369; seeds 100 grams 76.25; water content 7.848%; lactic acid 0.1125%; acetic acid 0.281%; reducing sugar 5.1065; total fat 50.70%; and cut test organoleptic test the preferred treatment by the panelists was Mixed Culture 5%.